A new criterion for the health risk assessment of Se and Pb exposure to residents near a smelter. (January 2019) - Zhou, Jun; Du, Buyun; Hu, Yuanmei; Liang, Jiani; Liu, Hailong; Fan, Xingjun; Zhang, Ligan; Cui, Hongbiao; Liu, Xiaoli; Zhou, Jing
Abstract: There is an increasing evidence linking protective effect of selenium (Se) against Pb toxicology; however, Pb exposure risk assessments usually consider only the environmental Pb contamination and dietary intake. Based on the current understanding of mechanisms of SePb interactions, the physiological function/toxicology of Se and the toxicology of Pb, a new criterion for Se and Pb exposure assessment is developed. Additionally, seven existing criteria were also used to assess the resident health risks around a smelter in China. The Pb concentrations in locally-produced foods exceeded the national tolerance limits of China and the Se in the foods were similar to those in areas with adequate Se levels. In accordance with the illustrated assessments of the new criterion and seven existing criteria, we found a large knowledge gap between the new and traditional assessments of exposure to Pb and/or Se. The new assessment criteria suggested that almost all the residents were facing the Se deficiency and 58% of the residents not only had the adverse health of Se deficiency, but also had the health risks of Pb toxicity. The Pb and Se in the hair and urine may partly support the new criterion. This study suggested that the process of Se counteracting the Pb toxicity may result in Se deficiency. Pb exposure combined Se intake should be considered in future assessments of Pb exposure (or Se intake). Graphical abstract: Image 1 Highlights: Lead exposure risk and selenium benefit-risk was assessed around a smelter. A new criterion is developed to assess exposure risks based on SePb interactions. A large knowledge gap is observed between the new and traditional assessments. All residents face Se deficiency and 58% face Pb exposure based on the new criteria. Abstract : A new criterion that considers both the toxicology of Pb exposure and the benefits and/or adverse health effects of Se intake, and seven existing criteria were used to assess the resident health risks.